Does Perceived of Risks and Benefits Drive Customers’ Intention to Share Information in Social Media? - Moderating Role of Customer Satisfaction - Hakim, Muhammad M (Universitas Bina Sarana Informatika, 2024)
Competition between companies is becoming more focused on the use of digital technology, including in marketing. Therefore, all companies need to understand all the things that can support the success of their marketing strategies, for example, encouraging free-advertising behavior by consumers in various digital media. In particular, this needs to be concerned by BRI (Bank Rakyat Indonesia), which until now is still considered slow in handling cases and customer complaints both offline and online. This study aimed to examine the influence of BRI customers’ perceived of risks and benefits on their intention to share information on social media, as well as the role of their satisfaction in this relationship. This study used a quantitative approach with a positivism paradigm. The data used was 262 data collected from BRI customers from May to August 2023 through an online survey mechanism. The data that has been collected was then analyzed using a moderation model path analysis involving control variables (age group, gender and educational level). Data analysis carried out using the SmartPLS program showed that: a) perceived of risks had a significant and negative effect towards intention to share information, both in the first and second models; b) perceived of benefits had a significant and positive effect towards intention to share information, both in the first and second models, and; c) customer satisfaction was not proven to play a moderating role in the relationship between perceived of risks and benefits toward intention to share information, both in the first and second models.